Hormonal treatment of dairy goats affected by hydrometra associated or not with ovarian follicular cyst - Souza, J. M G; Maia, A. L R S; Brandão, F. Z.; Vilela, C. G.; Oba, Eunice [UNESP]; Bruschi, J. H.; Fonseca, J. F. (Elsevier, 2013)
Hydrometra is considered a very important pathological condition, because it represents one of the main causes of temporary infertility in dairy goats. The objective was (i) to evaluate a protocol for the treatment of hydrometra associated (n=2) or not (n=17) with follicular ovarian cyst in 19 dairy goats and (ii) to assess its reproductive efficiency after treatment. For this purpose, 10. mg of dinoprost (PGF) divided in two equal doses were administered to all animals intravulvosubmucosally on Days 0 and 10. In addition, 500. IU hCG were administered on Day 7. Ultrasound exams were performed in all females from Days 0 to 3, 7 and 10 to 13 of treatment, in order to evaluate uterus drainage after each treatment. Goats were monitored for estrus after both treatments and mated after the second dose of PGF. Blood samples were collected from 11 goats to determine plasma progesterone concentrations before, during and after treatment. Of the 19 goats treated, 16 lost weight after the first dose, probably due to uterine discharge. Complete drainage of uterine fluid was observed in 11/19 (57.9%) and 17/19 (89.5%) after the first and second doses, respectively. Afterwards, we diagnosed 2 more goats with follicular cysts, for a total of 21.1% (4/19) of animals exhibiting hydrometra and ovarian cyst concomitantly. In one doe the diagnosis was on Day 2 and in the other on Day 11. All does showed progesterone concentrations superior to 1. ng/mL at Day 0, with an average of 10.6 ± 1.4. ng/mL. Out of the 10 goats mated, only two became pregnant after treatment, corresponding to 10.5% of the total (2/19). Although prostaglandin was effective to drain the uterine fluid and led to the onset of estrus, it did not improve the pregnancy rate. The use of hCG in female goats was not effective in luteinizing the cysts. It can be concluded that hydrometra alone or associated with ovarian follicular cyst may adversely affect goat reproductive performance. © 2012 Elsevier B.V.
Keywords: Caprine; Infertility; Progesterone; Pseudopregnancy; Ultrasonography; Animalia; Capra; Capra hircus; Hydrometra